Optimizing the extraction of oil from sugarcane bagasse using thermochemical liquefaction - Ang, George Herbert L. (Animo Repository, 2006)
Oil was extracted from sugarcane bagasse using thermochemical liquefaction without using reducing gas. Pulverized bagasse was mixed with water and with alkali catalysts, sodium carbonate and sodium formate. Bagasse slurry was processed for an hour at reaction temperatures of 473 K, 523 K, and 573 K, respectively. Results indicated that decreasing liquefaction temperature from 573 K to 473 K increases oil yields. In addition to that, energy recoveries of between 44.47% and 58.47% were attained. Moreover, 99% product conversion was achieved at a reaction temperature of 523 K. Statistical analysis also indicated that increasing temperature from 473 K to 573 K increases product quality and at the same time decreases product quantity. Furthermore, in a 573 K temperature setting, the calorific value of the extracted oil is 27.55 MJ/kg, which is similar with bituminous coals compared with corn oil and soybean oil methyl esters.